Cerebral Blood Flow in Severe Brain Injuries - A. V. Leonov (Общая реаниматология)
Objective: to study the effect of roncoleukin and gelofusin on cerebral circulation in victims with severe brain injury. Subjects and methods. A hundred and forty-seven patients with severe brain injury were examined. The patients were divided into 4 groups: 1) 41 patients received the standard treatment (a control group); 2) 35 patients had the standard treatment added by roncoleukin by a scheme; 3) 35 had the standard treatment and ron-coleukin supplemented with gelofusin; 4) 36 received the standard treatment and gelofusin solution. All the patients underwent monitoring: rheoencephalograms on days 1—3 and 10—14, daily determination of plasma viscosity by a VK-4 viscosimeter, and an immunogram. Results. Severe brain injury causes a 2—3-fold reduction in cerebral circulation and an increase in arterial and arteriolar tones. Along with a marked immunoprotective effect, roncoleukin improved cerebral circulation. The other agent (gelofusin) made blood rheological properties better. Co-administration of roncoleukin and gelofusion improved cerebral circulation more significantly than when the agents were used alone. There was normalization of arterial and arteriolar tones. Conclusion. The proposed treatment can be recommended for wide use in patients with severe brain injury. Key words: roncoleukin, gelofusin, brain injury.